2013
DOI: 10.1007/s11102-013-0500-6
|View full text |Cite
|
Sign up to set email alerts
|

Radically resected pituitary adenomas: prognostic role of Ki 67 labeling index in a monocentric retrospective series and literature review

Abstract: Ki-67 Labeling Index is an immunocytochemical marker of cell proliferation. The correlation of Ki-67 expression with pituitary adenomas recurrence has been investigated and is highly debated. Aim of this study was to evaluate whether Ki-67 correlates with recurrence even in patients with an apparently completely removed pituitary adenoma. We retrospectively reviewed the database of the Hypothalamic-Pituitary Disease Unit at the Catholic University of Rome, collected between 2003 and 2011. Inclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…In a previous work [22], in a series of 191 radically resected typical pituitary adenomas, we suggested that a Ki-67 value of 1.5% correlates with worse DFST. According to these previous data, we divided the study population of this series into two groups (group A: cases with a Ki-67 value <1.5%, and group B: cases with a Ki-67 value ≥1.5%) and, consequently, we analyzed epidemiological, clinical, histopathological, neuroradiological and prognostic features of pituitary adenomas with a Ki-67 expression higher and lower than 1.5%.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In a previous work [22], in a series of 191 radically resected typical pituitary adenomas, we suggested that a Ki-67 value of 1.5% correlates with worse DFST. According to these previous data, we divided the study population of this series into two groups (group A: cases with a Ki-67 value <1.5%, and group B: cases with a Ki-67 value ≥1.5%) and, consequently, we analyzed epidemiological, clinical, histopathological, neuroradiological and prognostic features of pituitary adenomas with a Ki-67 expression higher and lower than 1.5%.…”
Section: Resultsmentioning
confidence: 86%
“…Recurrence was defined as hormonal and/or radiological disease relapse in functioning pituitary adenomas and radiological disease relapse in nonfunctioning pituitary adenomas [18,19,20,21,22]. Progression was defined as regrowth in tumor size based on MRI and/or evidence of an increase in plasma hormone levels in partially resected secreting pituitary adenomas [14,23].…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies did not confirm the correlation of these criteria with clinical behavior and aggressiveness of each individual adenoma (4,5,6,7,8,9,10). In particular, the Ki-67 LI, widely used to determine cellular growth fraction in many types of tumors, is accepted as prognostic indicator in pituitary tumors, although controversial results have emerged from clinical studies and criticisms are also reported in the literature (6,11,12,13,14,15). Other markers have been proposed to assess the aggressiveness of PA, among which pituitary tumor transforming gene, p27, p16, galectin-3, and cyclin D1, but none of them has gained general acceptance as prognostic indicator (9,16,17,18,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells proliferation is an important biological parameter that reflects disease behavior, which might also predicts for disease prognosis. The nuclear protein Ki-67 is a proliferative marker and widely used prognostic indicator in several cancer diagnosis, including breast cancer, bladder cancer, gastrointestinal neuroendocrine tumor, oral cancer, lung cancer, astrocytoma, and pituitary adenoma [8][9][10][11][12]23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells proliferation is an important biological parameter that reflects disease behavior, which might also predicts for disease prognosis. The nuclear protein Ki-67 is a proliferative marker and widely used prognostic indicator in several cancer diagnosis, including breast cancer, bladder cancer, gastrointestinal neuroendocrine tumor, oral cancer, lung cancer, astrocytoma, and pituitary adenoma [8][9][10][11][12]23,24].In endometrial cancers, Ki-67 in addition to other biomarkers was found to be useful marker to distinguish benign proliferative conditions from cancer precursors and low grade endometrioid adenocarcinomas (16,25). In a study on 270 endometrial samples Ki-67 expression was found to be higher in samples with high-grade endometrioid carcinomas vs normal endometrial samples [26].…”
mentioning
confidence: 99%